Assessing the Impact of Internet of Everything Technologies in Football - Pires, Marcelo (2018)
Pires, M., & Santos, V. (2018). Assessing the Impact of Internet of Everything Technologies in Football. Journal of Sports Science, 6(1), 36-55. DOI: 10.17265/2332-7839/2018.01